IIBC - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The International Institute of Biological Control (IIBC) is a nonprofit organization which aims to support the development of biological control and integrated pest management worldwide. Since its establishment in 1927 IIBC has provided a unique...